2015
DOI: 10.1111/ipd.12180
|View full text |Cite
|
Sign up to set email alerts
|

‘Volumetric analysis of hand and rotary root canal instrumentation and filling in primary teeth using Spiral Computed Tomography’ – an invitro study

Abstract: Rotary root canal instrumentation may be indicated for utilization in primary teeth, for enhancing root canal preparation and good quality of root canal filling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 13 publications
1
26
0
1
Order By: Relevance
“…According to the present results, the null hypotheses for root canal volume and surface need to be rejected, since root canal preparation with both rotary file systems resulted in significantly greater increase in root canal volume and surface in both primary teeth and permanent teeth. These results confirm two recent studies evaluating the shaping effectiveness of different rotary files vs hand files in primary teeth . Presumably, the greater conicity of the rotary instruments compared with conventional hand files contributed to more dentine removal in the coronal region, resulting in greater post‐preparation root canal volume and surface area.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…According to the present results, the null hypotheses for root canal volume and surface need to be rejected, since root canal preparation with both rotary file systems resulted in significantly greater increase in root canal volume and surface in both primary teeth and permanent teeth. These results confirm two recent studies evaluating the shaping effectiveness of different rotary files vs hand files in primary teeth . Presumably, the greater conicity of the rotary instruments compared with conventional hand files contributed to more dentine removal in the coronal region, resulting in greater post‐preparation root canal volume and surface area.…”
Section: Discussionsupporting
confidence: 88%
“…These results confirm two recent studies evaluating the shaping effectiveness of different rotary files vs hand files in primary teeth. 8,26 Presumably, the greater conicity of the rotary instruments compared with conventional hand files contributed to more dentine removal in the coronal region, resulting in greater post-preparation root canal volume and surface area. As a result, the percentage of uninstrumented area in relation to the increase in volume and surface area was lower with the use of rotary file systems.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of laboratorial studies have employed ZOE as the gold standard obturation material, evaluating different filling techniques or different obturation materials on an isolated approach. Some studies used radiographs as evaluation method, resulting only in a bidimensional interpretation .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, rotary instrumentation dramatically reduces the working time, which is a very interesting aspect to consider for pediatric patients (1,(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, two recent studies (9,10) showed the use of computed tomography (CT) in the assessment of root canal preparation of primary teeth. Is noteworthy that although there are no studies that assess the biomechanical preparation in primary teeth using micro-computed tomography (micro-CT), this methodology has been commonly used for this purpose in permanent teeth, as it allows a three-dimensional noninvasive assessment of the RCS and root canal preparation (12,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%